Use of Tenecteplase in Acute Ischemic Stroke : A Systematic Review of Randomized Controlled Trials and Primary Studies - Bayu Aji Perdana; Mega Siti Fasicha (International Medical Journal Corp. Ltd, 2026)
Background: Tenecteplase (TNK), a bioengineered variant of alteplase with superior fibrin specificity, prolonged plasma half-life, and single-bolus administration, has emerged as a promising alternative thrombolytic agent in acute ischemic stroke (AIS). The growing body of randomized controlled trial (RCT) evidence necessitates a comprehensive synthesis to guide clinical implementation. Objectives: To systematically evaluate the efficacy and safety of tenecteplase compared with alteplase or standard medical care in adult patients with AIS across multiple clinical scenarios, doses, and time windows, drawing upon all available high-quality RCT evidence. Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. RCTs and primary studies comparing tenecteplase with alteplase or standard medical care in AIS were eligible. Two independent reviewers performed screening, data extraction, and risk of bias assessment using the Cochrane Risk of Bias 2.0 (RoB 2) tool. Primary outcomes included excellent functional outcome (modified Rankin Scale [mRS] 0–1 at 90 days), functional independence (mRS 0–2), symptomatic intracranial hemorrhage (sICH), and 90-day mortality. Results: Seventeen primary studies enrolling over 11,800 patients met inclusion criteria. Tenecteplase at 0.25 mg/kg was non-inferior or superior to alteplase (0.9 mg/kg) for excellent functional outcome at 90 days across multiple large-scale RCTs (AcT, TRACE-2, ORIGINAL, ATTEST-2, TASTE). Updated meta-analysis confirmed TNK superiority for mRS 0–1 at 3 months (RR 1.05; 95% CI 1.01–1.10). Symptomatic intracranial hemorrhage rates were comparable (RR 1.12; 95% CI 0.83–1.53). Intravenous TNK prior to endovascular thrombectomy (BRIDGE-TNK) achieved significantly higher functional independence (52.9% vs. 44.1%; RR 1.20; 95% CI 1.01–1.43). Extended-window TNK (TRACE-III, TIMELESS) demonstrated benefit in selected patients. The 0.4 mg/kg dose was associated with increased hemorrhagic risk. Conclusion: Tenecteplase 0.25 mg/kg is non-inferior—and in several outcomes superior—to alteplase for AIS thrombolysis within 4.5 hours, with comparable safety. Single-bolus administration confers operational advantages. Tenecteplase should be considered the preferred thrombolytic agent in current AIS management, particularly in settings with endovascular capability.